Early rehabilitation challenges of surgical patients with COVID-19 infection – a single-arm study - Simić-Panić, Dušica; Bošković, Ksenija; Pantelinac, Slobodan; Knežević, Aleksandar; Jovićević, Predrag; Kozios, Apostolos; Janjić, Nataša; Nikolić, Nikola; Vojnović, Larisa; Tomašević-Todorović, Snežana (Vojnosanitetski pregled, 2024)
Background/Aim. A very limited amount of data regarding the rehabilitation outcome of surgical patients with COVID-19 is available in the current literature. The aim of this study was to point out the characteristics of early rehabilitation of these patients and determine the predictors of rehabilitation outcomes. Methods. The study was designed as a prospective clinical trial. It included patients who had surgical treatment from April 1, 2022, to March 31, 2023, at the University Clinical Center of Vojvodina, Serbia and either had positive results for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) preoperatively or developed coronavirus disease 2019 (COVID-19) within 72 hrs after surgery. The rehabilitation program was planned for each patient according to the type of surgical treatment, age, clinical presentation and severity of the COVID-19, length of immobilization, and comorbidities. Rehabilitation treatment (RT) started with a minimum of one 30-minute daily session, up to three 30-minute sessions daily. Patients were assessed at the beginning of RT and discharge. Outcomes were assessed with the Modified Borg Scale (MBS) for dyspnoea, Barthel index (BI) for activities of daily living, Six-Minute Walk Test (6MWT) for exercise tolerance, and Timed up and Go (TUG) test for balance and lower limb mobility. Results. A total of 81 patients were included in the study. RT  was successful for 42 patients (24 female and 18 male) with an average age of 62.10 ± 20.07 years. These patients exhibited significant functional improvement, which was measured by all tests that assessed rehabilitation outcome at discharge: BI (p
Keywords: covid-19; general surgery; rehabilitation; treatment outcome.